PENYULUHAN SERTIFIKASI BIJI KAKAO PADA KELOMPOK TANI SIAMASEI DI DESA TENGGELAN KECAMATAN LUYO KABUPATEN POLEWALI MANDAR - Indra Basir; Mujirin M Yamin; Wahyu Maulid Adha (Universitas Mataram, 2023)
Cocoa certification is regulated through the Decree of the Minister of Agriculture of the Republic of Indonesia Number 314/Kpts/KB.020/10/2015 concerning Guidelines for Production, Certification, Distribution and Supervision of Cocoa Plant Seeds (Theobroma cacao L.). The general aim of cocoa certification is to create sustainable agriculture to improve the welfare of farmers and at the same time provide a guarantee for consumers that the cocoa products they consume are obtained from sustainable sources. One of the cocoa producing areas in Polewali Mandar Regency is Luyo District, there are several farmer groups that have not participated in the cocoa certification program. One of the farmer groups that has not participated in this program is the Siamasei Farmer Group. The Siamasei Farmers Group was founded in 2005 through establishment Decree Number 6/04/10/2002/KTH.147/2005. This service activity is to increase the knowledge of the farmer group members’ knowledge of the Siamasei Farmer Group members about the cocoa bean certification program from the egulation aspect, what the certification procedures are and the economic benefits of the program. The method of implementing service is training and mentoring with a chronological strategy. The first stage is questions and answers related to the problems faced by the Siamasei Farmers Group, the second stage the service team provides counseling material, then the third stage is sharing samples of certified cocoa and the fourth stage is monitoring and evaluation. The benefit and hope of this service activity is to increase the Siamasei Farmers Group’s understanding of the Cocoa bean product certification program. Apart from that, group members can increase the economic value of the cocoa bean products they produce. The expected result of this service activity is increased understanding of the Siamasei Farmers Group regarding the Cocoa bean product certification program. Apart from that, group members can increase the economic value of the cocoa bean products they produce.